تعليم مهارة القراءة في ضوء النظرية البنائية الاجتماعية لفيجوتسكي (Vigotsky) دراسة الحالةفي جامعة بالنجكارايا الإسلامية الحكومية - Aulia Mustika Ilmiani (Imtiyaz : Jurnal Pendidikan dan Bahasa Arab, 2018)
AbstractOne of the lecturers in the Department of Arabic at IAIN Palangka Raya teaches the reading using newest way and innovation compared to the previous ones. The innovation contains a variety of learning materials, learning strategies and learning evaluation.From this phenomenon, the researcher concluded that in reading skill teaching as done by one of the lecturers at IAIN Palangka Raya, there are some indicators of learning that are based on Vigotsky’s social constructivism theory in which it focuses on the roles of the students and social interaction in learning between the lecturers and the students or interaction among students.The aim of this research is to describe reading skill learning performed by the third semester students of IAIN Palangka Raya in 2016-2017 Academic Year. By looking the phenomena in the field in the perspective of processes, activities and interactions during teaching and learning process.This study is classified as descriptive qualitative research using case study design at IAIN Palangka Raya in 2016-2017.Techniques of data collecton in this research include interview, observation and documentation. The data  should be examined by using triangulation.The results of the study can be explained as follows: First, the goal of the teaching reading skill to the third semester students of  IAIN Palangka Raya 2016-2017 in the perspectivesof Vygotsky’ social constructivism theory; it can be seen from lecturer’s explanations towards reading skill focusing on discussion together with her students. Discussion is a kind social interactions between the lecturer and her students and social interactions among students. Second, learning materials of learning of reading skill in the view of of Vygotsky’ social constructivism theory, can be seen also from lecturer’s explanation which are relevant to students’ everyday life and their experiences around them. The materials to be used are based on the consideration of the purpose, prior knowledge, time and available place, and the numbers of students who follow the lesson. Third, the strategy of learning in the view of Vygotsky’s social constructivism theory,  can be seen from the strategy used by the lecturer such as; cooperative learning strategy, top down processing strategy and discovery learning strategy. These three strategies stress on the roles and the activeness of students in the learning-activities. Fourth, the evaluation of learning of reading skill in the view of Vygotsky’s social constructivism theory can be seen from the learning evaluation of reading skill as applied by the lecturer. The evaluation not only tests and examines one aspect of the skill, but also covers all aspects of the shill at once. Test of reading skill, not only deal with reading skill but also it covers other skills such as speaking skill, writing skills, structure and translation.